Ferroptosis in neurodegenerative diseases: mechanisms and therapeutic potential of stem cell derivatives - Zhang, Ting; Zhang, Yusu; Xie, Jinpeng; Lu, Dandan; Wang, Lihong; Zhao, Shuaifei; Zhou, Jing; Cheng, Yang; Kou, Ting; Wang, Jue; Chen, Ying; Xu, Lei; et al. (Frontiers in Cell and Developmental Biology, 2025)
Ferroptosis, a non-apoptotic, iron-dependent form of regulated cell death, is closely related to the pathogenesis of neurodegenerative diseases. Stem cells and their derivatives exhibit remarkable potential in modulating ferroptosis, offering promising therapeutic intervention for neurodegenerative diseases. In this review, we systematically explore neurological aging and its association with cognitive impairment and neurodegenerative diseases, with focus on the molecular mechanisms of ferroptosis in neurodegenerative diseases and the potential therapeutic strategies of stem cell derivatives for neurological diseases.